Comparing the Effectiveness of Elsa Speak and ESP for Teaching Speaking to Students with Different Self-Confident - Hafiza Namira; Suwandi Suwandi (Universitas Negeri Semarang, 2023)
Remote learning is a modern learning model that is a solution for people who have constraints of time, place, and human resources, especially during the pandemic who are required to learn and teach online without face-to-face. In SMA Negeri 16 Medan, the English teacher taught students with speaking material, and the teacher teaches, discusses, and practices through Zoom Meeting and assigned assignments to students via WhatsApp Group. The researcher found out the good or bad influence on remote learning through Zoom or WhatsApp Groups. This research explained how significant the students’ achievement learning by using Elsa Speak and ESP platforms conducted with high and low self-confidence of students in learning speaking. The research design was a quantitative approach with a 2x2 factorial design involving the tenth-grade students SMA N 16 Medan, as the research participants. The students’ different self-confidence was taken as a factor that might influence the platform. Two experimental classes were held on different platforms: Elsa Speak and ESP. The independent variables are Elsa Speak and ESP. Students' confidence levels influenced the platform, and data collection involved observation, questionnaires, and speaking tests. To answer the hypotheses, the data were analyzed using pair statistics, and independent statistics. Based on the analysis Elsa Speak in high and low self-confidence is a more effective in learning platform than ESP.